Immunity As A Booster of Iraqi EFL Teachers' Energy: A Correlational Study - Waqid Maki Numan (Hasanuddin University, 2025)
Teachers have the power to change their students' lives for the better; therefore, teachers should be armed with some skills to become more effective and successful ones. However, Teachers' Immunity (TI) is defined as a robust armoring system one with high-intensity threats and allows teachers to maintain professional equilibrium and instructional effectiveness. Thus, the present study aimed at examining the probable association between EFL teachers' immunity as a booster for Iraqi EFL teacher’s energy. To this end, two scales of Teacher Immunity Questionnaire (TIQ) and Teacher Energy Questionnaire (TEQ) administered among 100 Iraqi EFL teachers comprising of 28 females and 72 males. Besides, SPSS program 26 and Pearson Correlation was utilized to analyze data. It sounds that concerning the provided definitions of both scales plus the findings, the more immune the EFL teachers are, the more energized they are in handling their job satisfactorily. Moreover, the significant role of language teacher immunity as predictor of EFL teachers was discovered throughout this study and significant and meaningful relationship between EFL teachers' immunity as a booster of energy was found using Pearson correlation (Sig=0.000). The implications of the present study may shed new light on the significance of incorporating teacher immunity approach into teacher development programs as a core subject as well as teacher energizer.